An Evaulation of the BO'SUN Multi-Beam Sonar System - Burke, R.; Robson, J. (The International Hydrographic Review, 2015)
This report describes the evaluation of the BO'SUN Multi-Beam Sonar System carried out by the Hydrographic Development Section, Atlantic Region. The BO'SUN System, a product of the Harris Division of General Instrument Corporation, forms 21 adjacent narrow beams to give a crosstrack coverage of 2.6 times depth. Digitized slant-range measurements along with navigation data are recorded on magnetic tape in computercompatible format. A software package is available to process, edit, and contour the data. A survey of Bedford Basin was carried out with sufficient line spacing to ensure 100% bottom coverage. A contoured chart was computer generated from over two million depth measurements made by the BO'SUN System. Comparison of the BO'SUN contour chart with an existing chart produced by using conventional hydrographic techniques showed the contours in general agreement. Although some differences were noted, the larger number of soundings, greater coverage, and narrower beam widths of the BO'SUN System reflected greater contour detail than would be possible to obtain from the field sheet of the conventional survey.